ANALISIS EFEKTIVITAS PENGHIMPUNAN DAN PENYALURAN ZAKAT PRODUKTIF DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN PADANG LAWAS - Maya Dian Eka Sari; Saparuddin Siregar; Budi Dharma (ITB AAS Indonesia Surakarta, 2023)
Productive Zakat is the allocation of zakat money to beneficiaries (Mustahik) which is used to develop their business in order to meet their daily needs in a sustainable manner and is not directly used for consumption needs. The purpose of this study was to determine the effectiveness of the collection and distribution of productive zakat at the National Amil Zakat Agency (BAZNAS) in Padang Lawas Regency. This research is a descriptive qualitative research and literature review using data collection techniques through interviews and documentation. While to measure effectiveness with the measurement of Zakat Core Principle (ZCP). The results of the study indicate that the effectiveness of the collection and distribution of productive zakat in the National Amil Zakat Agency (BAZNAS) of Padang Lawas Regency by measuring the effectiveness of the distribution of zakat core principle (ZCP), then the ACR category in 2022 is Effective. The proportion of zakat funds distributed in the 2022 period amounted to 85.95%. This shows that zakat institutions have the ability to collect and distribute effectively, because the distribution of funds in the National Amil Zakat Agency (BAZNAS) of Padang Lawas Regency is 85.95% in 2022. Keywords : Effectiveness, Collection, Distribution, Productive Zakat